Assessing The Legal And Human Rights Validity Of Applying The Death Penalty For Serious Child Sex Offenders - Daming, Saharuddin; Husna, Mufidatul; Fadilah, Chika (JURNAL MAHASISWA YUSTISI, 2026)
The increase in the cases and severity of child molestation by predators has attracted public concern. Public to promote law enforcers to apply the death penalty for perpetrators of serious sexual crimes against children to create a deterrent effect. Unfortunately, this public aspiration was rejected by the Indonesian National Human Rights Commission and the Bandung district court on the grounds that the death penalty is contrary to human rights and violates the 1945 Constitution. This research uses an interdisciplinary legal method, combining doctrinal and sociolegal research. This study aims to examine the validity of the law as well as human rights principles and norms against the rejection and acceptance of the death penalty in Indonesia. The results showed that law enforcement and human rights instituted by the special courts for perpetrators of serious sexual crimes against children are not in line with the elements of legal validity and human rights.